THE ASSOCIATION BETWEEN HUMAN GIARDIASIS AND ABO AND RHESUS BLOOD GROUPS - Al-Taie, Lazim; Al-Mayah, Kasim; Thweni, Abdul-Jalil (Iraqi Journal of Science, 2024)
Giardia lamblia is considered as one of most parasites that causes diarrhea in human. The present study aimed to investigate the relationship between giardiasis and ABO and Rhesus blood groups among local population. ABO and Rhesus blood groups were determined for 94 patients who gave positive result for Giardia infection. The ABO and Rhesus blood groups of these patients were compared with those of 196 non infected patients.The frequency of ABO and Rhesus blood groups in infected patients does not differ significantly from those in non infected patients. ABO and Rhesus blood groups may not interfere with Giardia infection.